Framing Media Dalam Kontroversi Video Syur Rebecca Klopper : (Studi Kasus Pemberitaan Suara.com) - Mawi Sari Rajagukguk; Dwi Aji Budiman (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
In May, September and October 2023, the Indonesian people were shocked by the circulation of an exciting video allegedly by Rebecca Klopper. Within three months, this scandal became trending and was widely searched for, causing online media to compete to report on this case. By using sensational narratives, journalists try to attract readers' interest without considering the impact on the victims. The depiction of news is called framing, in this case the researcher will look at how news writers create their news using the framing model of Zhongdang Pan and Gerald M. Kosicki. The research method used is descriptive qualitative with Sara Mills discourse analysis. The online media that is quite intensively highlighting this case is Suara.com, where this media tends to use Rebecca Klopper to attract readers' attention. This certainly shows that the media tends to blame the women in the video while the men are less highlighted. By taking advantage of Rebecca's position as an artist, journalists are able to create narratives that influence netizens' views of Klopper. It cannot be denied that this happened because of the demands of each online media editor to create sensational titles in order to attract clicks from the public.